When should orthostatic blood pressure changes be evaluated in elderly: 1st, 3rd or 5th minute?. (July 2016) - Soysal, Pinar; Aydin, Ali Ekrem; Koc Okudur, Saadet; Isik, Ahmet Turan
Highlights: Evaluation of orthostatic hypotension should be a part of geriatric assessment. 1st minute measurement might1 be adequate and effective to assess OH in elderly. 1st minute measurement shortens duration of evaluation might be more convenient. Abstract: Detection of orthostatic hypotension (OH) is very important in geriatric practice, since OH is associated with mortality, ischemic stroke, falls, cognitive failure and depression. It was aimed to determine the most appropriate time for measuring blood pressure in transition from supine to upright position in order to diagnose OH in elderly. Comprehensive geriatric assessment (CGA) including Head up Tilt Table (HUT) test was performed in 407 geriatric patients. Orthostatic changes were assessed separately for the 1st, 3rd and 5th minutes (HUT1, HUT3 and HUT5, respectively) taking the data in supine position as the basis. The mean age, recurrent falls, presence of dementia and Parkinson's disease, number of drugs, alpha-blocker and anti-dementia drug use, and fasting blood glucose levels were significantly higher in the patients with versus without OH; whereas, albumin and 25-hydroxy vitamin D levels were significantly lower (p < 0.05). However, different from HUT3 and HUT5, Charlson Comorbidity Index and the prevalence of diabetes mellitus were higher, the use of antidiabetics, antipsychotics, benzodiazepine, opioid and levodopa were more common (p < 0.05). Statistical significance of the number of drugs and fasting blood glucose level was prominent in HUT1 as compared to HUT3 (p < 0.01, p < 0.05). Comparison of the patients that had OH only in HUT1, HUT3 or HUT5 revealed no difference in terms of CGA parameters. These results suggests that orthostatic blood pressure changes determined at the 1st minute might be more important for geriatric practice. Moreover, 1st minute measurement might be more convenient in the elderly as it requires shorter time in practice.